1999
DOI: 10.1063/1.371787
|View full text |Cite
|
Sign up to set email alerts
|

Effects of as-quenched structures on the phase transformations and magnetic properties of melt-spun Pr7Fe88B5 ribbons

Abstract: Phase transformations and magnetic properties of overquenched Pr7Fe88B5 ribbons during annealing have been investigated. X-ray diffraction and Mössbauer measurement indicate that melt spinning at different wheel velocities caused the as-quenched ribbons to have distinctive structures. Depending on their as-quenched structure, the phase transformation of the ribbons during annealing may take place in one of the following sequences: (1) amorphous phase (Am)+Pr2Fe14B+α-Fe→Pr2Fe14B+α-Fe; (2) Am+α-Fe→Am′+α-Fe→α-Fe+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(19 citation statements)
references
References 15 publications
2
17
0
Order By: Relevance
“…Hence, fewer, but larger, ␣-Fe crystals would be expected in the former than in the latter [24]. TEM studies on these alloys [17,21] provide evidence to support this proposition the OQA alloys having a unimodal distribution of grain sizes centred at ∼40 nm, in contrast to the DQ alloys which showed a clearly bimodal distribution with one peak centred at ∼15 nm, corresponding to ␣-Fe, and another centred typically at ∼40-45 nm, corresponding to the RE 2 Fe 14 B grains. The coarser ␣-Fe crystallites in the OQA samples may not be completely exchange coupled to the adjacent 2/14/1 grains which would account for the inferior second quadrant loop shapes observed in those alloys.…”
Section: Properties Of Nanophase Melt Spun Prfecob Alloys Processed Bmentioning
confidence: 95%
See 1 more Smart Citation
“…Hence, fewer, but larger, ␣-Fe crystals would be expected in the former than in the latter [24]. TEM studies on these alloys [17,21] provide evidence to support this proposition the OQA alloys having a unimodal distribution of grain sizes centred at ∼40 nm, in contrast to the DQ alloys which showed a clearly bimodal distribution with one peak centred at ∼15 nm, corresponding to ␣-Fe, and another centred typically at ∼40-45 nm, corresponding to the RE 2 Fe 14 B grains. The coarser ␣-Fe crystallites in the OQA samples may not be completely exchange coupled to the adjacent 2/14/1 grains which would account for the inferior second quadrant loop shapes observed in those alloys.…”
Section: Properties Of Nanophase Melt Spun Prfecob Alloys Processed Bmentioning
confidence: 95%
“…The influence of the RE concentrations on J r , i H c and (BH) max for Nd y Fe 94−y B 6 [9], Pr y Fe 94−y B 6 [15][16][17] and (Nd 0.75 Pr 0.25 ) y Fe 94−y B 6 [18] alloys for approximately constant d g of RE 2 Fe 14 B phase, lying in the range 20-35 nm, are shown in Fig. 1.…”
Section: Effects Of Re Concentration On the Magnetic Properties Of Ndmentioning
confidence: 99%
“…4,5 Such nanocomposite microstructure is usually prepared by crystallization of amorphous alloys. [7][8][9] However, the crystallization mechanism and phase transition still remain unclear now, because of the involved many factors that make the crystallization behavior quite complex. One most important factor is the wheel speed of rapid quenching, since it affects the initial phase structures of the as-quenched alloys.…”
Section: Introductionmentioning
confidence: 99%
“…One most important factor is the wheel speed of rapid quenching, since it affects the initial phase structures of the as-quenched alloys. 10 Zhou has studied similar systems and found that the decomposition of metastable phase depended on the wheel speed, 7 but did not have further explanation. We have studied the relationship between the magnetic properties and the wheel speed, and found that samples prepared by mid-speed had the best magnetic properties.…”
Section: Introductionmentioning
confidence: 99%
“…For amorphous RE-Fe-B ribbon alloys (RE contento11.7 at%) the microstructure evolution, occurring in the course of annealing, starts with precipitation and growth of a-Fe [5][6][7], followed by crystallization of the RE 2 Fe 12 B phase. The a-Fe crystallites are large, which leads to reduction of the exchange interactions [5,8].…”
Section: Introductionmentioning
confidence: 99%